School attendance problems and absenteeism as early warning signals: review and implications for health-based protocols and school-based practices - Kearney, Christopher A.; Dupont, Randolph; Fensken, Michael; Gonzálvez, Carolina (Frontiers in Education, 2023)
School attendance has been historically linked to healthy states of functioning, whereas school attendance problems/absenteeism have been historically linked to unhealthy states of functioning. Indeed, school attendance and its problems are deeply embedded within multiple domains of functioning at both analytic and systemic levels. This article utilizes complex systems theory and the concept of early warning signals to illustrate how changes in school attendance could indicate instability and perhaps sudden transitions to unhealthy states of functioning for students, families, schools, and communities. The article reviews how school attendance problems/absenteeism intersect with functioning at analytic (academic, social-emotional, mental health, physical health, family) and systemic (school and community) levels. The article also includes recommendations for how viewing changes in school attendance as early warning signals could improve health-based protocols (enhancing access to care; integrating systems of care) and school-based practices (developing multi-tiered systems of support models and community asset maps; modifying educational and policy perspectives). A primary theme involves more streamlined efforts to identify movement from healthy to unhealthy states among individuals to assign proactive and personalized treatment avenues (health-based protocols) and among systems to enact needed intervention supports and reforms (school-based practices).